Anaplastic large cell lymphoma associated to breast implants in Latin America: Linfoma anaplásico de células grandes asociado a implantes mamarios en Latinoamérica - Ugarte, Gianella Fernanda (2024)
Dear Editor, After reading the 2023 publication by Manjarres A. et al. in your esteemed journal on cancer and breast implants, I would like to contribute additional data regarding breast implant-associated anaplastic large-cell lymphoma (BIA-ALCL) in Latin America. This work highlights the lack of knowledge and evidence in Latin American countries, a crucial aspect given the classification of BIA-ALCL as a new pathological entity by the World Health Organization in 2016 (1).